Characteristics of the Physical Literacy of Preschool Children - Agnese Kretaine; Helena Vecenane (Education Sciences)
Recent research in the area of physical literacy has revealed that the early years are a period that has not been well studied. Our research team designed a deductive review with the aim of investigating how preschool children’s physical literacy manifests across affective, physical, cognitive and social domains. The review includes scientific publications from the last four years, which investigate the elements of physical literacy in preschool children: motivation, confidence, motor competence, knowledge, understanding and use of physical activity. The characteristics of the elements were systematised into four domains, affective, physical, cognitive and social, as engagement in physical activities. Results. The majority of the articles explained physical literacy behaviours in 4- to 5-year-old children. The physical domain was most frequently described, mainly including the three basic motor skills of postural stability, object control, and locomotion, as well as physical qualities of movement. The second most frequently described domain was the social domain of the application of physical activities in preschool stages, including the types and amounts of physical activity used in both organised and leisure time. Conclusions. Physical literacy of preschool children is a purposefully organised and guided process, during which a child is given the opportunity to try and apply age-appropriate movement skills, without being limited by the child’s gender, parental attitudes, sporting choices, or the traditions of sport culture.